Are gastrointestinal parasites associated with the cyclic population dynamics of their arctic lemming hosts?. (December 2019) - Gilg, Olivier; Bollache, Loïc; Afonso, Eve; Yannic, Glenn; Schmidt, Niels Martin; Hansen, Lars Holst; Hansen, Jannik; Sittler, Benoît; Lang, Johannes; Meyer, Nicolas; Sabard, Brigitte; Gilg, Vladimir; et al.
Abstract: Many rodents, including most populations of arctic lemmings (genus Dicrostonyx and Lemmus ), have cyclic population dynamics. Among the numerous hypotheses which have been proposed and tested to explain this typical characteristic of some terrestrial vertebrate communities, trophic interactions have often been presented as the most likely drivers of these periodic fluctuations. The possible role of parasites has, however, only seldom been assessed. In this study, we genetically measured the prevalence of two endoparasite taxa, eimerians and cestodes, in 372 faecal samples from collared lemmings, over a five year period and across three distant sites in Northeast Greenland. Prevalence of cestodes was low (2.7% over all sites and years) and this taxon was only found at one site (although in 4 out of 5 years) in adult hosts. By contrast, we found high prevalence for eimerians (77.7% over all sites and years), which occurred at all sites, in every year, for both age classes (at the Hochstetter Forland site where both adult and juvenile faeces were collected) and regardless of reproductive and social status inferred from the characteristics of the lemming nests where the samples had been collected. Prevalence of eimerians significantly varied among years (not among sites) and was higher for juvenile than for adult lemmings at the Hochstetter Forland site. However, higher prevalence of eimerians ( P t ) was only associated with lower lemming density ( N t ) at one of the three sites and we found no delayed density dependence between N t and P t+1 to support the parasite hypothesis. Our results show that there is no clear relation between lemming density and eimerian faecal prevalence in Northeast Greenland and hence no evidence that eimerians could be driving the cyclic population dynamics of collared lemmings in this region. Graphical abstract: Image 1 Highlights: Prevalence of eimerians and cestodes was measured in collared lemming in Greenland. Prevalence of cestodes was low (2.7%; one site only) compared to eimerians (78%). Prevalence of eimerians was higher for juveniles and varied among years. Prevalence of eimerians was negatively associated with lemming density at one site. lack of delayed density dependence does not support the parasite hypothesis for lemming cycles.